Pleistocene evolution of the coccolith morphology and flux in the Tropical Indo-Pacific associated with climatic simulations - Beaufort, Luc; Bolton, Clara T; Sarr, Anta-Clarisse (PANGAEA, 2024)
Data describing the Pleistocene history of the morphology and the accumulation rate of Noelaerhabdaceae (Genus Emiliania, Gephyrocapsa, Reticulofenestra and Pseudoemiliania) coccoliths, measured in 9 Tropical Indo-Pacific sequences retrieved during IODP (Exp353 and Exp363) and IMAGES (expedition 3 and 13) expeditions (MD05-2920, MD05-2930, MD97-2140, U1443, U1446, U1448, U1483, U1485, and U1486). The morphology parameters considered are the length (size in µm) and the mass (in pg) of the coccoliths. From those parameter are index of morphologic divergence has been calculated. Those values are presented in different tables in the way that has been used to contract the different figure of Beaufort et al., Nature, 2021. The climatic simulations tables present the variability of the ocean-atmosphere system in response to eccentricity and its impact on ocean biogeochemistry. This dataset contains atmosphere, ocean and ocean biogeochemistry outputs from modeling experiments with variable orbital configurations that target the effect of eccentricity on the climate system (Beaufort et al. 2021). The simulations have been run using the IPSL-CM5A2 General Circulation Model (Sepulchre et al. 2020 - GMD). It includes 7 simulations with pre-industrial boundary conditions (CO2, ice-sheet, paleogeography) and different set of realistic eccentricity/precession/obliquity configurations (at 2.222, 2.230, 2.265, 2.346, 2.369, 2.380 and 2.395 Ma).
Keywords: Coccolithophores; eccentricity; evolution; general circulation model; morphology; ocean biochemistry; Paleoclimate; Pleistocene; Topical